ACG Clinical Guideline: Alcoholic Liver Disease. (February 2018) - Singal, Ashwani K; Bataller, Ramon; Ahn, Joseph; Kamath, Patrick S; Shah, Vijay H
Abstract : N/A: Alcoholic liver disease (ALD) comprises a clinical‐histologic spectrum including fatty liver, alcoholic hepatitis (AH), and cirrhosis with its complications. Most patients are diagnosed at advanced stages and data on the prevalence and profile of patients with early disease are limited. Diagnosis of ALD requires documentation of chronic heavy alcohol use and exclusion of other causes of liver disease. Prolonged abstinence is the most effective strategy to prevent disease progression. AH presents with rapid onset or worsening of jaundice, and in severe cases may transition to acute on chronic liver failure when the risk for mortality, depending on the number of extra‐hepatic organ failures, may be as high as 20–50% at 1 month. Corticosteroids provide short‐term survival benefit in about half of treated patients with severe AH and long‐term mortality is related to severity of underlying liver disease and is dependent on abstinence from alcohol. General measures in patients hospitalized with ALD include inpatient management of liver disease complications, management of alcohol withdrawal syndrome, surveillance for infections and early effective antibiotic therapy, nutritional supplementation, and treatment of the underlying alcohol‐use disorder. Liver transplantation, a definitive treatment option in patients with advanced alcoholic cirrhosis, may also be considered in selected patients with AH cases, who do not respond to medical therapy. There is a clinical unmet need to develop more effective and safer therapies for patients with ALD.